2006
DOI: 10.1021/nl061684x
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiar Electronic Structure of PbSe Quantum Dots

Abstract: PbSe is a pseudo-II-VI material distinguished from ordinary II-VI's (e.g., CdSe, ZnSe) by having both its valence band maximum (VBM) and its conduction band minimum (CBM) located at the fourfold-degenerate L-point in the Brillouin zone. It turns out that this feature dramatically affects the properties of the nanosystem. We have calculated the electronic and optical properties of PbSe quantum dots using an atomistic pseudopotential method, finding that the electronic structure is different from that of ordinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
235
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 168 publications
(259 citation statements)
references
References 34 publications
24
235
0
Order By: Relevance
“…Liljeroth et al were able to measure the density of states of single PbSe nanocrystals directly using scanning tunnelling spectroscopy and suggested that transition b corresponds to the 1P h -1P e transition. [13] Below we will compare the experimental absorption spectra and their features with an absorption spectrum that we obtained by tight-binding calculations, as well as an absorption spectrum that was recently calculated by An et al [1] As will become clear, there are still important discrepancies between the experimental data and both theoretical calculations. The purpose of this comparison is to give an overview of the current understanding of the absorption spectrum of PbSe QDs, not to give a final answer on the correct assignment of the different transitions.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Liljeroth et al were able to measure the density of states of single PbSe nanocrystals directly using scanning tunnelling spectroscopy and suggested that transition b corresponds to the 1P h -1P e transition. [13] Below we will compare the experimental absorption spectra and their features with an absorption spectrum that we obtained by tight-binding calculations, as well as an absorption spectrum that was recently calculated by An et al [1] As will become clear, there are still important discrepancies between the experimental data and both theoretical calculations. The purpose of this comparison is to give an overview of the current understanding of the absorption spectrum of PbSe QDs, not to give a final answer on the correct assignment of the different transitions.…”
Section: Resultsmentioning
confidence: 87%
“…The assignment of the optical transitions is subject to considerable debate in the literature. [1,[10][11][12][13] This debate largely focuses on the assignment of the "second" peak in the absorption spectrum, labelled b here. Based on theoretical calculations of the energy levels and experimental work, this feature has previously been assigned to the 1S h -1P e (or 1P h -1S e ) transition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations